ZnAl2O4‐Functionalized Zinc Oxide Microstructures for Highly Selective Hydrogen Gas Sensing Applications. Issue 7 (14th February 2018) - Hoppe, Mathias; Lupan, Oleg; Postica, Vasile; Wolff, Niklas; Duppel, Viola; Kienle, Lorenz; Tiginyanu, Ion; Adelung, Rainer
Abstract : In this work, a simple method of ZnAl2 O4 ‐functionalization of ZnO microstructures is presented. The different characterization methods (structural, chemical, and micro‐Raman) demonstrated the presence of only ZnO and ZnAl2 O4 crystalline phases. ZnAl2 O4 nano‐crystallites grow on the surfaces of ZnO 3D microstructures having diameters of 50–100 nm and with high density. Transmission electron microscopy (TEM) and high‐resolution TEM (HRTEM) results clearly show ZnAl2 O4 crystallites functionalizing zinc oxide tetrapod arms. The individual structures (microwires (MWs) and three‐dimensional (3D) tetrapods (Ts)) are integrated into functional devices, suitable for gas sensing applications. All devices show excellent hydrogen gas selectivity at relatively low operating temperature in the range of 25–100 °C. The highest gas sensing performances are obtained based on individual ZnAl2 O4 ‐functionalized ZnO tetrapods (ZnAl2 O4 /ZnO‐T, with an arm diameter ( D ) of ≈400 nm) and a response of ≈2 at 25 °C to 100 ppm of hydrogen gas (H2 ), while a ZnAl2 O4 /ZnO‐MW ( D  ≈ 400 nm) shows only a response of ≈1.1. The Al‐doped ZnO MW ( D  ≈ 400 nm) without ZnAl2 O4 elaborated in another work, chosen only for comparison reason, shows no response up to 800 ppm H2 gas concentration. A gas sensing mechanism is proposed for a single ZnAl2 O4 /ZnO‐T microstructure based sensor. The obtained results on ZnAl2 O4 /ZnO‐T‐based devices is superior to many reported performances of other individual metal oxide nanostructures with much lower diameter, showing promising results for room temperature H2 gas sensing applications. Abstract : A simple method to improve gas sensing properties of the ZnO individual structures by surface functionalization with ZnAl2O4 nanoscopic crystals is reported. Synthesized hybrid microstructures can serve as a novel material for developing high performance and highly selective room temperature hydrogen gas sensors.